Neophyllobius lorestanicus sp. nov. and N. ostovani sp.nov. (Acari: Camerobiidae) from Iran - Khanjani, Mohammad; Hoseini, Mohammad Ahmad; Yazdanpanah, Shima; Masoudian, Farshad (Zootaxa, 2014)
Two new species of the genus Neophyllobius Berlese, 1886 are described: Neophyllobius lorestanicus sp. nov. collected from soil under Prunus domestica L. (Rosaceae) in Markazi province and Neophyllobius ostovani sp. nov. from soil and rotten leaves of oak trees in Fars province, Iran. A key to all known Iranian and Turkish species of Neophyllobius is provided.